World economic development - Fryer, Donald W. (New York, McGraw-Hill, 1965)
This book provides an analysis of the complex and ever changing world economy. The book is divided into 5 sections: the pattern of world economic development; agriculture, forestry, and fishing; mining and manufacturing industries; services industries; and conclusion.
Includes bibliographies.
lje 18/09/2018
Loans
Keywords: Economic history; Economic growth; Economic development